The Development of Reflective-Scientific Learning Model to Improve 21st Century Learning Skills In Historical Learning - Musa Pelu (AGASTYA: JURNAL SEJARAH DAN PEMBELAJARANNYA, 2021)
This research aims to develop the Reflective-scientific Learning Model to accommodate 21st-century learning skills in learning history. The ADDIE instructional design was used as the research method to develop the learning model. The research participants were 120 senior high school students. The Reflective-scientific Learning Model consists of five learning stages: historical engagement, critical-exploration, communicative-explanation, creative-elaboration, and reflective evaluation. The research results prove the feasibility and effectiveness of the developed learning model in improving students' 21st-century learning skills in the learning history process. It means that the developed learning model can accommodate the needs of the 21st-century learning skills and the learning history objectives. Based on this research, the authors highlight that the elaboration of the learning model can provide a space for synchronizing learning history objectives with other educational concepts from various disciplines. Thus, further research and development in the history education landscape should provide more opportunities for elaborating the learning models to amend the role and impact of learning history in the 21st century.